Al-Zahraa School 1911-1949 (historical study) (Journal of the College of Basic Education, 2023)
The city of Kadhimiya (the holy) bequeathed several generations with feet in science and leaders who established their works in the land. It was necessary to study these works, the most prominent of which is the Al-Zahra School. Then came our research tagged “Al-Zahra School 1911-1949 a historical study” that the importance of this research is based on the study of the school and shed light on the Its location, its building, its most important teachers and students, its name, as well as its historical development over the years that Iraq has experienced. The research is divided into an introduction, a conclusion, three sections, and a list of sources. The first topic included the most important religious schools in the (holy) city of Kadhimiya, which bore the title “The Historical Roots of Religious Schools in Kadhimiya City until 1911.” Its building, its most important teachers, students, school planning, and Islamic architecture in its construction, which bore the title “Al-Zahra School, its inception and development until 1949.” As for the third topic: it included the school’s positions on: the British occupation of Iraq (1914-1918), the Twentieth Revolution, and the treaty The Iraqi-British 1922, titled "The Al-Zahra School's Position on Internal Developments in Iraq Until 1949".